Classification of Daily Living Activities in subjects with Parkinson’s Disease using Artificial Neural Networks - Rodriguez Montero, Lizeth; Ambrosio Bastián, Jose; Pérez Sanpablo, Alberto Isaac (Revista Mexicana de Ingenieria Biomedica, 2024)
This paper is a proposal to contribute with health specialists to enrich the follow-up and support systems in patients with Parkinson’s by identifying and classifying Daily Living Activities (DLAs) using Artificial Neural Networks programmed in Python language. The proposed method of supervised learning allowed the classification of 6 DLAs through 22 signals obtained from the application of Principal Component Analysis, creating a database used to train a Multilayer Perceptron. This model achieved an approximation of classification with 93% of the F1-score. The present study demonstrates the versatility of ANNs based on MLP combined with the PCA technique since, even in an unbalanced database such as the one used, it allows excellent values to be achieved in the F1-score measure. The use of Artificial Intelligence and other tools applied in this work may eventually help specialists to perform a more accurate assessment in the monitoring of rehabilitation for patients with Parkinson’s disease by improving records and thus avoiding subjectivity in the interpretation of treatment results.